Serum Neurofilament Light Is Elevated Differentially in Older Adults with Uncomplicated Mild Traumatic Brain Injuries - Iverson GL; Reddi PJ; Posti JP; Kotilainen AK; Tenovuo O; Ohman J; Zetterberg H; Blennow K; Luoto TM (MARY ANN LIEBERT, INC, 2025)
Neurofilament light (NF-L) might have diagnostic and prognostic potential as a blood biomarker for mild traumatic brain injury (mTBI). However, elevated NF-L is associated with several neurological disorders associated with older age, which could confound its usefulness as a traumatic brain injury biomarker. We examined whether NF-L is elevated differentially following uncomplicated mTBI in older adults with pre-injury neurological disorders. In a case-control study, a sample of 118 adults (mean age = 62.3 years, standard deviation [SD] = 22.5, range = 18-100; 52.5% women) presenting to the emergency department (ED) with an uncomplicated mTBI were enrolled. All participants underwent head computed tomography in the ED and showed no macroscopic evidence of injury. The mean time between injury and blood sampling was 8.3 h (median [Md] = 3.5; SD = 13.5; interquartile range [IQR] = 1.9-6.0, range = 0.8-67.4, and 90% collected within 19 h). A sample of 40 orthopedically-injured trauma control subjects recruited from a second ED also were examined. Serum NF-L levels were measured and analyzed using Human Neurology 4-Plex A assay on a HD-1 Single Molecule Array (Simoa) instrument. A high correlation was found between age and NF-L levels in the total mTBI sample (r = 0.80), within the subgroups without pre-injury neurological diseases (r = 0.76) and with pre-injury neurological diseases (r = 0.68), and in the trauma control subjects (r = 0.76). Those with mTBIs and pre-injury neurological conditions had higher NF-L levels than those with no pre-injury neurological conditions (p < 0.001, Cohen's d = 1.01). Older age and pre-injury neurological diseases are associated with elevated serum NF-L levels in patients with head trauma and in orthopedically-injured control subjects.